A high-resolution multiband survey of Westerlund 2 with the Hubble Space Telescope. III. The present-day stellar mass function - Zeidler, Peter; Grebel, Eva K.; Pasquali, Anna (The astronomical journal, 2017)
We present a detailed analysis of the spatial distribution of the stellar population and the present-day mass function (PDMF) of the Westerlund 2 (Wd2) region using the data from our high-resolution multiband survey with the Hubble Space Telescope . We used state-of-the-art artificial star tests to determine spatially resolved completeness maps for each of the broadband filters. We reach a level of completeness of 50% down to ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn1.gif] $F555W=24.8$ mag ( ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn2.gif] $0.7\,M_ødot $ ) and ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn3.gif] $F814W=23.3$ mag ( ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn4.gif] $0.2\,M_ødot $ ) in the optical and ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn5.gif] $F125W=20.2$ mag and ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn6.gif] $F160W=19.4$ mag (both ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn7.gif] $0.12\,M_ødot $ ) in the infrared throughout the field of view. We had previously reported that the core of Wd2 consists of two clumps: namely the main cluster and the northern clump. From the spatial distribution of the completeness-corrected population, we find that their stellar surface densities are ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn8.gif] $1114\,\mathrmstars\,\mathrmpc^-2$ and ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn9.gif] $555\,\mathrmstars\,\mathrmpc^-2$ , respectively, down to ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn10.gif] $F814W=21.8$ mag. We find that the PDMF of Wd2 has a slope of ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn11.gif] $\rmΓ =-1.46± 0.06$ , which translates to a total stellar cluster mass of ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn12.gif] $(3.6± 0.3)· 10^4\,M_ødot $ . The spatial analysis of the PDMF reveals that the cluster population is mass-segregated and most likely primordial. In addition, we report the detection of a stellar population of spatially uniformly distributed low-mass ( ##IMG## [http://ej.iop.org/images/1538-3881/153/3/122/ajaa55c0ieqn13.gif] $\lt 0.15\,M_ødot $ ) stars, extending into the gas ridges of the surrounding gas and dust cloud, as well as a confined region of reddened stars, likely caused by a foreground CO cloud. We find hints that a cloud-cloud collision might be the origin of the formation of Wd2.
Gesehen am 30.08.2017